SmartVisual: a visualisation tool for SmartThings IoT Apps using static analysis. Issue 4 (1st August 2020) - Bak, Na-Yeon; Chang, Byeong-Mo; Choi, Kwanghoon
Abstract : SmartThings is one of the most widely used smart home platforms for the internet of things (IoT). SmartApps are IoT applications on the SmartThings platform that enables automation of home devices. SmartApps are event‐driven; inputs are received from device events, and outputs are issued to control devices. Understanding the behaviour of IoT applications is a challenge because the inputs and outputs are rarely visible. To tackle the challenge, the proposed approach is to visualise IoT applications as a set of IoT services. The authors propose an event‐flow‐based visualisation method where a flow from an event to action is viewed as an IoT service. The authors implement a tool called SmartVisual that performs a static analysis on SmartApps to generate a diagram of event flows. The tool also provides a tree model of the static structure of SmartApps and software metrics relevant to the event‐driven nature. The tool was applied to 64 SmartApp samples provided by SmartThings. Each SmartApp had four event flows on average, although the most complex SmartApp had 58 event flows, and two inputs and two outputs, and the average length of the event flows was 1.43 methods.